2022
DOI: 10.1177/20552076221084469
|View full text |Cite
|
Sign up to set email alerts
|

A new path to address health disparities: How older Aboriginal & Torres Strait Islander women use social media to enhance community health (Protocol)

Abstract: Background Digital health offers a fresh avenue to address health disparities experienced by Aboriginal and Torres Strait Islanders. Despite the scant evidence about how Aboriginal and Torres Strait Islanders access and use health technology, the Australian government has prioritised research that uses technology to enable people to manage their health and promote better health outcomes. Older Aboriginal and Torres Strait Islander women are cultural leaders in their communities, enabling them to provide valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The AHWs engaged with the learning material and teaching approaches, which enabled a supportive and flexible learning environment to be created. It has been reported in other studies that Aboriginal people are early adopters of technology and partners in digital health programs and research [44,45]. In this study it was reported that using VoIP technologies enabled information to be paced and different teaching techniques applied to thoroughly explore specific aspects of COPD.…”
Section: Online Educationmentioning
confidence: 77%
“…The AHWs engaged with the learning material and teaching approaches, which enabled a supportive and flexible learning environment to be created. It has been reported in other studies that Aboriginal people are early adopters of technology and partners in digital health programs and research [44,45]. In this study it was reported that using VoIP technologies enabled information to be paced and different teaching techniques applied to thoroughly explore specific aspects of COPD.…”
Section: Online Educationmentioning
confidence: 77%